Comparison of Functional Outcomes of High Tibial Osteotomy and Unicompartmental Knee Arthroplasty in Patients with Medial Knee Osteoarthritis - Cigercioglu, Nazli; Ozer, Hamza; Baltaci, Gul (The Journal of Knee Surgery, 2025)
Unicompartmental knee arthroplasty (UKA) and high tibial osteotomy (HTO) surgeries are often preferred in individuals with medial knee osteoarthritis (OA). The aim of the study was to compare the functional outcomes of patients with UKA and HTO. Seventy-seven individuals were included in the study, of which 39 individuals had undergone HTO surgery (median age = 58.38 ± 7.99, median body mass index [BMI] = 30.93 ± 3.33 kg/m2) and 38 individuals had undergone UKA surgery (median age = 62.95 ± 7.74 years, median BMI = 30.48 ± 3.57 kg/m2). Pain was evaluated before and after surgery. Pain severity, 6-Minute Walk Test (6MWT), 10-Repetition Sitto-Stand Test (10 × STS), stairs test, Timed Up and Go (TUG), and Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire were used for functional evaluation. There were no differences in demographic characteristics between groups (p > 0.05). The HTO group had lower postoperative pain (p = 0.043) and KOOS pain subscale scores (p = 0.043), better stairs test (p = 0.041), and 10 × STS results (p = 0.007). There were no significant differences between the groups in terms of the 6MWT, TUG, and KOOS total scores (p > 0.05). The results showed that individuals who underwent HTO surgery experienced less postoperative pain and had better functional levels compared with those who underwent UKA surgery. It shows that good functional performance can be achieved with HTO surgery in early medial compartment OA.
Keywords: knee osteoarthritis; high tibial osteotomy; unicompartmental knee arthroplasty; functional performance